Peer Victimization and Nonsuicidal Self Injury: Social Support as a Potential Protective Factor for Adolescents - Afifah, Nursita; Asih, Sali Rahadi; Kuntoro, Ike Anggraika (Psychological Research on Urban Society, 2025)
Nonsuicidal self-injury (NSSI) is a high-risk behavior that increases the desire and likelihood of attempting to commit suicide. Peer victimization has been found to precede NSSI. Both phenomena are prevalent among adolescents living in urban areas. This cross-sectional study investigated the role of social support in the relationship between peer victimization and NSSI. A total of 449 adolescents who lived in urban areas completed the Deliberate Self-Harm Inventory (DSHI), Multidimensional Peer Victimization Scale (MVPS), and Multidimensional Scale of Perceived Social Support (MSPSS) to assess NSSI frequency, peer victimization, and perceived social support. The results found that NSSI is higher in girls. While boys experienced more peer victimization, they also perceived more social support. Early adolescents were the most vulnerable to peer victimization and NSSI. NSSI tended to be higher in adolescents whose parents were divorced. Results also showed that social support moderated the effects of peer victimization on NSSI (b = −.021, 95% CI [−.037, .006], p = .007). Family support lessens the impact of peer victimization on NSSI. The interaction between family support and peer victimization significantly explains the 13% variance of NSSI. Interaction between friends and support from significant others with peer victimization was not significant in predicting NSSI.